FAKTOR FAKTOR KRUSIAL DALAM MANAJEMEN PEMBELAJARAN SEJARAH DI MASA PANDEMI (STUDI PADA JURUSAN PENDIDIKAN SEJARAH UNIMA) - Imbar, Meike; Mesra, Romi (Jurnal Ilmiah Mandala Education (JIME), 2022)
In the online teaching and learning process during the pandemic at the Unima History Education Department, of course the success of this learning process depends on the successful collaboration between all parts into a learning system that carries out their respective functions well so that learning objectives will be achieved properly. Furthermore, the issue of core factors that are indeed very vital if not properly regulated or organized where these factors significantly affect the achievement of learning objectives during this pandemic. The purpose of this study is to reveal the Crucial Factors in the Management of History Learning in the Pandemic Period (Studies at the Department of History Education, Unima). The method used is a qualitative research method. The results of this study are; The Crucial Factors in the Management of History Learning in the Pandemic Period (Studies at the Department of History Education at Unima) are as follows; driving factors: the Unima learning management system (LMS), the quota subsidy from the government, lecturers and students have plenty of time to prepare for online learning from their homes. Inhibiting factors: the available facilities are inadequate, there are still many lecturers who are not technology literate, lecturers and students have to learn a lot about the digital world, some students cannot access learning tools and media, and it is difficult for lecturers to supervise student learning activities.